Understanding Sharia-Compliant Stock Invesment In Indonesia: A Descriptive Phenomenological Study Based On Secondary Data - Gregorius Peitra Dirgantara Sakti Nikula Asmara (PT. Samudra Solusi Profesional, 2024)
The development of Sharia-compliant capital markets has become an integral part of the broader expansion of Islamic finance, particularly in Muslim-majority countries such as Indonesia. Sharia-compliant stocks are designed to provide investment opportunities that align with Islamic principles, emphasizing ethical conduct, prohibition of interest-based activities, and avoidance of speculative transactions. Despite significant institutional growth and regulatory support, the practical understanding and perceived meaning of Sharia-compliant stock investment among market participants remain underexplored, especially from a qualitative perspective. Most existing studies rely heavily on quantitative performance analysis, offering limited insight into the normative and experiential dimensions of Sharia compliance. This study aims to explore the phenomenon of Sharia-compliant stock investment in Indonesia using a qualitative descriptive phenomenological approach based entirely on secondary data. The research draws upon peer-reviewed academic literature, regulatory documents issued by financial authorities and Sharia councils, and official statistical publications to capture the shared meanings and interpretations embedded in existing discourse. By synthesizing these sources, the study seeks to identify how Sharia-compliant stocks are conceptualized, justified, and critically assessed within the Indonesian Islamic finance ecosystem. The findings indicate that Sharia-compliant stocks are commonly understood as a hybrid instrument that integrates religious values with modern financial practices. However, variations in Sharia screening standards, limited investor literacy, and concerns regarding the substantive ethical impact of such instruments present ongoing challenges. The study also reveals tensions between normative Islamic economic objectives and the technical implementation of Sharia compliance in capital markets. This research contributes to Islamic finance literature by providing an interpretive framework that complements dominant quantitative approaches. Practically, it offers insights for regulators, policymakers, and educators to strengthen Sharia capital market development through improved transparency, harmonized standards, and enhanced investor education. The study further serves as a conceptual foundation for future qualitative research involving primary data collection.